Textos de apresentação em livros didáticos de português: processos de objetivação do sujeito aluno - Carvalhaes, Wesley Luis (2009)
The purpose of this work is to discuss the Portuguese textbook (LDP – Livro Didático de Português) using their introductory texts as references. These texts are viewed as processes for reaching the student-subject and are based upon theoretical and analytical principles of the Discourse Analysis (AD – Análise do Discurso). This research is part of the requirements for the Master’s Degree program at the Federal University of Goiás Language and Linguistics School. It covers the introductory texts in four distinct moments: 1) before 1980; 2) the 1980’s; 3) the 1990’s, and 4) from 2000 to 2006. Not all of the selected textbooks incorporate introductory texts, what reveals a discourse that confirms the student-subject. This study historically depicts the Discourse Analysis as a field of expertise connected to the language studies. It makes a historical survey of the textbooks in general, especially the LDP, analyzing the introductory texts under the lights of the discourse theories, identifying the student subject-form presented in, and by, the investigated texts. The introductory texts were written in diverse ways, since the discourses, the discourse formations, and the imaginary formations modified themselves due to social-historical relations. As a consequence of this movement, the figure of the student was subject to a metamorphosis through each text. Therefore, changes in the discourses become guidelines to the. These transformations in the discourse are materialized by the introductory texts, bringing up LDP concepts such as the profile of the student, and the language and Portuguese teaching in each period. These text analysis allow for multi-angled results: 1) language as an abstract set of rules and as an instrument of communication; 2) language as a way of social interaction, 3) language viewed as from being a reproduction of linguistic models, supervised by the teacher, to a significant activity; 4) the student faced as from both a source and receptacle for information, to acting protagonist of the process for the construction of knowledge. The introductory texts show a notion of language and language teaching, and delineate an image of the student. However, it is necessary to assume a critical view regarding the manner the LDP sees the student, accepting that these images are close either to discourse formations common to the school environment or to the world of editorial business. This research contributes to the area of school practice, especially the teaching of Portuguese, approaching the textbooks as both conditioning and determining elements, especially regarding the configuration of quite a subjective element: the student.